A budget of algal production and consumption by herbivorous fish in an herbivore fisheries management area, Maui, Hawaii. Issue 8 (30th August 2017) - Kelly, Emily L. A.; Eynaud, Yoan; Williams, Ivor D.; Sparks, Russell T.; Dailer, Meghan L.; Sandin, Stuart A.; Smith, Jennifer E.
Abstract: The relative rates of carbon fixed by primary producers vs. consumption by primary consumers shape the community of organisms in ecosystems. On coral reefs, it is important to understand the demography of algae, given known competitive dynamics with reef‐building corals. Numerous studies have shown that fleshy algal abundance is enhanced in the absence of top‐down control by herbivores on coral reefs. However, fewer studies have quantified and compared rates of production by the benthic fleshy algal community and consumption by herbivores. Here, we estimate a budget for fleshy algal growth and herbivorous fish consumption on a Hawaiian coral reef based upon integration of field‐measured and taxonomically specific variables. Data were collected at Kahekili Herbivore Fisheries Management Area, Maui, established in 2009, in which taking of herbivorous fish and urchins is prohibited. Daily algal production was determined by quantifying benthic community composition, standing stock of algal biomass, and growth rates of common algal components. Consumption was determined using distributions of biomass and size classes of herbivorous fish species, consumption rates of herbivores on different algal species, and herbivore bite sizes. Our results show that throughout the first five years of herbivore protection, algal production consistently exceeded the grazing capacity of the herbivorous fish assemblage, but by a diminishing margin since 2010 (consumption 20.8% of production) to the end of the study in 2014 (consumption 67.0% of production). Further, larger size classes of herbivorous fishes in the scraper/excavator herbivore guild contributed more to consumption in later years, which could have additional feedbacks that promote reef‐building taxa. Projecting the budget using data from a neighboring decades‐long protected herbivorous fish assemblage indicated that the production and consumption budget for Kahekili could become balanced in future with continued management.